Non-boserupian ecology and agricultural risk : ethnic politics and land control in the arid southwest. - Davis Stone, Glenn (American Antropological Association, 1999)
Numerous cases of increasing population without fallow shortening or intensification without population pressure have been cited as disproof of the Boserup model of agricultural change. In this paper we argue that the model is an efficient explanation for agricultural change but only when certain agroecological conditions are met: higher marginal input costs must be both necessary and sufficient to raise production. Elsewhere, conditions are non-Boserupian, and other kinds of responses should be expected. Wupatki, a prehistoric agricultural frontier, is a case in point. Boserupian intensification was mostly impossible here, and with population influx, fanners turned instead to sociopolitical means of protecting the land base for extensive agriculture. A contemporary example from Nigeria illustrates territorial control by groups consolidated along ethnic lines. The strategy of relying on increasing numbers and monumental construction to back up territorial claims had unintended long-term consequences that led to abandonment of Wupatki.